A CLINICAL STUDY TO COMPARE THE EFFECT OF LEKHNIYA MAHAKASHAY THROUGH ORAL ADMINISTRATION AND SARWANG SWEDAN IN CASES OF STHAULYA W.S.R TO OBESITY (AYUSHDHARA, 2018)
Today 2.1billion people nearly 30% of world population are either obese or overweight. The rise in global obesity rates over the last 3 decades has been wide spread presenting a major public health epidemic both for the developed and developing world. In Ayurveda obesity is referred as Sthaulya. Excessive truncal adiposity is very well correlated with risk for diabetes, hypertension and cardiovascular disease obese people are 20% more likely to develop pancreatic cancer, number of GI disorder and hepatobiliary disorder. Mostly obesity is primary i.e., no obvious cause exists other than imbalance in energy intake and energy expenditure. Importantly modest losses of 5% to 10% of body weight have been shown to reduce health risk such as hyperlipidemia, hypertension and insulin resistance. In this research drugs are selected from Ayurvedic classics and the effect of Lekhaniya mahakashay is compared in Sarwang swedan as well as in oral medication. Overall goals of this weight loss management are, to prevent further weight gain, to lose weight to achieve a realistic target BMI and to maintain a lower body weight over the long term.